Pathogenic vibrios in the oyster Crassostrea virginica in the lagoon system of Mandinga, Veracruz, Mexico - Christian Reyes-Velázquez (Hidrobiológica, 2010)
Oyster consumption has been associated to the transmission of pathogenic bacteria, including those from the genus Vibrio. The objective of this investigation was to determine the concentrations of Vibrio parahaemolyticus and V. alginolyticus in Crassostrea virginica from the lagoon system of Mandinga, Veracruz, and their relationships with salinity and water temperature. Only the periods of greater production and consumption of oysters were examined: the dry and rainy seasons during 2008. Four sampling sites were selected, from which three samples were collected per site per season, resulting in a total of 24 samples. Each sample consisted of 30 oysters of commercial size that were subsequently analyzed using serial dilution. Biochemical analysis of the resulting bacterial colonies revealed concentrationsof V. parahaemolyticus and V. alginolyticus ranged from < 3 to 150 MPN/g. A positive correlation was observed between temperature and the concentration of V. parahaemolyticus (r = 0.69, p < 0.05), while the correlation with salinity was negative (r = -0.68, p < 0.05). No significant correlations between the concentration of V. alginolyticus and water temperature and salinity were observed for the rainy season. The main contribution of this paper is to establish safe areas and periods for oyster extraction.